Visionary of the principal leadership in improving the quality of learning - Atika, Murti; Harapan, Edi; Rohana, Rohana (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
Through education, it is hoped that future generations will have the skills, talents, and attitudes of quality that can respond to competition in the age of globalization. In order to increase the quality of learning, the innovative leadership of school principals has a significant role to play.The goal of this study was to explain the principal's vision of improving the standard of learning and the barriers to visionary leadership at SMA Negeri 1 BabatSupat. In this research, through questionnaire, evaluation and observation, using qualitative approaches and data collection techniques. Data analysis used data reduction, data presentation and vehicle analysis in this research Conclusion or verification. The authenticity of creditable, transferable, defensible and verifiable data the findings showed that : (1) The principal's vision of enhancing the standard of learning at SMA Negeri 1 BabatSupat is to realize: "The realization of Indonesian people with character, achievement, competitive and friendly insight" (2) Students succeed in academic and non-academic fields through the vision introduced by the principal. (3) The quality of learning through the leadership vision of the principal has guided school staff, especially educators, in the preparation of lesson plans according to the 2013 curriculum and the implementation of learning as a learning resource using current learning media in schools.(4) The challenges faced by the innovative leadership of the principal in enhancing the quality of learning in terms of the quality of teachers in learning are as follows: (1) lack of facilities for learning services that teachers can use in schools; (2) there are still some teachers who do not have teacher certificates, i.e. as many as 6 PNS teachers out of 17 current PNS teachers.